(untitled) (Palíndromo, 2020)
o analyze the insertion of urban intervention in exhibition spaces, the article focuses on a set of three interventions performed by the brazilian artist Guga Ferraz in public spaces – Ônibus Incendiado (2003), Cidade Dormitório (2007) and Até Onde o Mar Vinha, Até Onde o Rio Ia (2010-2014) -, investigating the different tactics used by the artist to present these works in museums, galleries or cultural centers.